PERANCANGAN APLIKASI PEMESANAN PRODUK TOKO TERATAI MOTOR BERBASIS MOBILE MENGGUNAKAN FRAMEWORK FLUTTER - Surbakti, Samuel Sinarta; Mochamad Adhari Adiguna (PT Triputra Sejahtera Prima, 2023)
Teratai Motor is a motorcycle equipment shop located in the Tangerang area. Teratai Motor is engaged in the motorcycle automotive sector and focuses on selling motorized vehicle spare parts. The process of selling products is currently done manually and through several sales platforms. The sales process on other platforms has drawbacks, one of which is that every transaction made on the platform will be subject to a large discount and it is difficult to find a Teratai Motor store because there are many other sellers on the platform. To overcome this problem, the authors conducted research to create a sales application for the Teratai Motor shop with the aim of attracting more enthusiasts and overcoming the problem of cutting costs per transaction on each product sale. In developing this application the author uses the prototype method so that the writer can interact with users to overcome misunderstandings between users and writers. In making this application the author uses the Flutter framework. In the final stages of this research, the application will be tested using the black box, white box method and testing will be carried out on targets which will be carried out by the method of collecting data through questionnaires which will be processed by calculating the Likert scale. The results obtained from the testing phase of this application can be concluded that the functions in this application are running well and the results of testing on targets conclude that this application meets user needs with an average of 67.5%.